Effect of Aminoguanidine Intervention on Neutrophils in Diabetes Inflammatory Cells Wound Healing - Tian, M.; Qing, C.; Niu, Y.; Dong, J.; Cao, X.; Song, F.; Ji, X.; Lu, S. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To explore aminoguanidine (AG) effect on neutrophil functions and associated signal transduction way in diabetic rats wound healing. Sprague-Dawley (SD) rats were divided into 3 groups, Group A (control+burns), Group B (diabetes+burns), Group C (diabetes+burns+AG). Wound skin tissue was harvested at 6h, 24h and 36h after trauma, and then immunohistochemistry was used to detect AGE (advanced glycation end products) contents and RAGE (receptor of AGE) expression. Western blotting was applied to detect RAGE and NF-κB. Oxidative stress changes were detected by colorimetry. Inflammatory cytokines were determined by ELIASA and cell apoptosis by TUNEL. Pathological changes were analyzed by hematoxylin-eosin (HE) staining. In the wound tissue of Group C, compared to that in Group B, AGE content, RAGE expression level, NF-κB level declined, and MPO (myeloperoxidase) decreased at 36h; TNFα, IL-8, H2O2, GSH-Px (Glutathione peroxidse), and MDA (malondialdehyde) levels increased; dense post-traumatic inflammation belt formed obviously. AG for prophylactic use can promote the migration and respiratory burst of neutrophils markedly, and help to restore the functions of neutrophil; and the abnormal secretion of inflammation cytokines can be corrected partly. Blocking AGE deposition and promoting microenvironment were effective ways for diabetic wound healing.
Keywords: aminoguanidine; neutrophils; diabetic wound healing